National treaty law and practice - Hollis, Duncan B., 1970-; Blakeslee, Merritt R., 1946-; Ederington, Benjamin (Studies on the law of treaties, 2005)
"This book, which is dedicated to the memory of the distinguished international lawyer Monroe Leigh, presents a consolidated treatise on how different states organize their treaty-making through national law and practice."--Jacket